Bean, Moth—Vigna aconitifolia (Jacq.) Marechal - James M. Stephens (EDIS)
This document discusses the moth bean (Vigna aconitifolia), a drought-resistant legume primarily grown in India but also tested in Texas and California. The plant is described as ground-hugging with yellow flowers and short pods. Moth beans thrive in hot weather and can be grown in various seasons in Florida. In India, the pods and seeds are consumed as vegetables, with seeds containing 22-24% protein, though some protein is unavailable due to a trypsin inhibitor. Original publication date April 1994.